Analytical investigation and improvement of performance of a proton exchange membrane (PEM) fuel cell in mobile applications - Khazaee, Iman (Zielona Góra: Uniwersytet Zielonogórski)
In this study, the performance of a proton exchange membrane fuel cell in mobile applications is investigated analytically. At present the main use and advantages of fuel cells impact particularly strongly on mobile applications such as vehicles, mobile computers and mobile telephones. Some external parameters such as the cell temperature, operating pressure of gases and air stoichiometry affect the performance and voltage losses in the PEM fuel cell. Because of the existence of many theoretical, empirical and semi-empirical models of the PEM fuel cell, it is necessary to compare the accuracy of these models.
Keywords: PEM fuel cell; performance; semi-empirical; mobile application